Effect of aqueous extract of olive (Olea europaea) fruit on lipid profile in female rabbits (Baghdad Science Journal, 2025)
The activity of the aqueous extract of Olea europaea was tested at concentrations of 8, 15 or 20 mg/kg of body weight on lipid profile in twenty female local rabbits. These animals were randomly divided into four groups (five animals in each group). Three groups were dosed orally with the concentrations mentioned above, while the last was administered with distilled water and considered as a control group. These animals were orally dosed by aqueous extract using a micropipette for 30 days. The results showed that there was a significant (P